Disease burden and patient reported outcomes among patients with moderate to severe psoriasis: an ethnography study - Narayanan S; Guyatt V; Franceschetti A; Hautamaki EL (Dove Medical Press, 2014)
Siva Narayanan,1 Victoria Guyatt,2 Alessandra Franceschetti,3 Emily L Hautamaki1 1Ipsos Healthcare, Columbia, MD, USA; 2Ipsos Ethnography Centre of Excellence (ECE), London, UK; 3Ipsos Healthcare, London, UK Objectives: To assess the impact of psoriasis on health-related quality of life (HRQoL).Methods: An ethnographic study of patients with moderate to severe psoriasis was conducted in the US, France, Germany, Italy, Spain, UK, Brazil, and Canada to explore patients' views on treatment and the impact of psoriasis on HRQoL. Anthropologists and ethnographers spent a minimum of 5.5 hours with each consented patient and filmed their behaviors in everyday situations. Visual data and notes were analyzed to identify HRQoL-related themes.Results: The study included 50 adult patients. Patients described their appearance with disgust and self-loathing. Frustration was expressed due to a perceived lack of control of their lives. Prior to initiation of biologic treatment, daily rituals absorbed a good part of their day, including applying creams, checking one's appearance, and covering the body. Due to a lack of cultural discourse and patient's difficulty in articulating the impact of psoriasis, partners and family did not know how to react nor did they realize the full extent of the problem, and many patients experienced perceived social discrimination due to psoriasis, leaving them with feelings of isolation. Patients established on biologic treatment noticed a significant physical improvement and regained confidence, but psychosocial impacts, including social isolation, remained.Conclusion: This ethnographic study vividly depicted the unarticulated and emotional impact of psoriasis on the everyday lives of patients and presents an effective method of assessing HRQoL in chronic diseases.Keywords: psoriasis, health-related quality of life, ethnography, patient reported outcomes, conceptual model